The A home resident and family connected nursing system using virtual live video call application (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Many elderly people are hospitalised or cared for in a nursing home. They are more likely to go into delirium if they are separated from their loved ones. Even if video call is likely to lessen their tension, people may feel oppressed by a frequent video call and be reluctant to take the bother to call each time. Despite the lack of a strong familial bond in the living room, one individual may start a discussion with another at any moment and the conversation will naturally terminate without a clear indication. Using video calls, we provide a virtual living room system for connecting individuals who live far apart. A believe word is used to re-establish a connection to the other person after the video is disconnected.